Motivating Students to Learn How to Write Code Using a Gamified Programming Tutor - Simon Grey; Neil A. Gordon (MDPI AG, 2023)
Engagement and retention are widely acknowledged problems in computer science and more general higher education. The need to develop programming skills is increasingly ubiquitous, but especially so in computer science where it is one of the core competencies. Learning to write code is a particularly challenging skill to master, which can make retention and success even more difficult. We attempt to address student engagement within an introductory programming module by attempting to motivate students using a gamified interactive programming tutor application that provides immediate feedback on the student's work. In this paper, we describe the design of the gamified programming tutor application, along with a related topology to characterize student engagement. We discuss the design of the software, the gamified elements, and the structured question design. We evaluate the engagement with the gamified programming tutor of two cohorts of students in the first year of a computer science programme, with over two hundred students taking part. We attempt to frame this engagement in terms of frequency, duration, and intensity of interactions, and compare these engagement metrics with module performance. Additionally, we present quantitative and qualitative data from a survey of students about their experience using the programming tutor application to demonstrate the efficacy of this approach.